2019
DOI: 10.33021/firm.v4i1.682
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Entrepreneurial Culture on Entrepreneurial Intention Among Business Students

Abstract: The number of entrepreneurs in Indonesia increased in 2017 from 1.67% to 3.10% from 225 million Indonesians. But the number is still less than the number of our neighboring entrepreneurs, Malaysia has 6% entrepreneurs, Singapore 7% and Thailand 5%. Increasing the number of entrepreneurs shows the increasing economic growth of a country, therefore the government made various efforts encourages the growth of the number of entrepreneurs in Indonesia, through education in this case the ministry of education provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 0 publications
1
21
0
4
Order By: Relevance
“…Entrepreneurship education has been recognized as one of the important determinant of entrepreneurial intentions. Various studies like Galloway and Brown (2002), Kuratko (2005), Potter et al (2017), Fayolle and Gailly (2008), Patricia and Silangen (2016), Ndofirepi and Rambe (2017), Senjaya and Genoveva (2019) and Genoveva (2019) empirically demonstrated the entrepreneurial education as an important determinant of business orientation. Several previous studies by the authors concluded that there is influence of some factors on business orientation of business students, such as cultural factors, family support, self-efficacy, motivation, and e-commerce (Genoveva, 2019;Senjaya and Genoveva, 2019).…”
Section: Literature Review and Legislative Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Entrepreneurship education has been recognized as one of the important determinant of entrepreneurial intentions. Various studies like Galloway and Brown (2002), Kuratko (2005), Potter et al (2017), Fayolle and Gailly (2008), Patricia and Silangen (2016), Ndofirepi and Rambe (2017), Senjaya and Genoveva (2019) and Genoveva (2019) empirically demonstrated the entrepreneurial education as an important determinant of business orientation. Several previous studies by the authors concluded that there is influence of some factors on business orientation of business students, such as cultural factors, family support, self-efficacy, motivation, and e-commerce (Genoveva, 2019;Senjaya and Genoveva, 2019).…”
Section: Literature Review and Legislative Backgroundmentioning
confidence: 99%
“…While, gender has an influence on entrepreneurial desires, entrepreneurial women have better performance than male (Djajagunawan and Genoveva, 2018). Among some researchers who explain groups that have family businesses have higher entrepreneurial intention than those who do not have a family business (Genoveva, 2019;Chrisman, Chua and Steier, 2003;Nandamuri and Gowtami, 2013).…”
Section: A Demographicmentioning
confidence: 99%
See 3 more Smart Citations